Responsible research and innovation actions in science education, gender and ethics : cases and experiences /: cases and experiences. ([2018]) - Ferri, Fernando; Dwyer, Ned; Raicevich, Saša; Grifoni, Patrizia, 1959-; Altiok, Husne; Andersen, Hans Thor; Laourēs, Giannēs; Silvestri, Cecilia
No abstract available